Preparation and characterization of a highly specific affinity ultrafiltration membrane for trypsin separation - Sofiah Hamzah (Terengganu: Universiti Malaysia Terengganu, 2013)
This study aimed to develop a highly specific affinity ultrafiltration membrane for trypsin separation. The research has been divided into three major stages; (1) Fabrication of basic membrane for affinity support, (2) Membrane surface modification using chitosan and (3) Further modification of the chitosan/PSf membrane for affinity purpose